INTERSECTIONALITY AND MEDIA BIAS: GENDER AND IDENTITY FRAMING IN JOURNALISM OF FEMALE POLITICIANS IN AMERICAN NEWS OUTLETS - Ikhwan, Azzadina N; Halimi, Sisilia Setiawati (ppjbsip, 2025)
Despite the number reaching an all-time high in the most recent election, female participation in U.S. politics has its drawbacks. One longstanding issue that continues to occur today is media bias, which often manifests in news coverage. Media bias plays a crucial role in shaping public perceptions of female politicians, intertwining aspects of gender, socio-economic status, and political ideology. This study critically examines the media coverage of Alexandria Ocasio-Cortez by American left-leaning and right-leaning outlets through the lens of intersectionality. Employing critical discourse analysis, it reveals how semantic choices and thematic patterns perpetuate identity-driven biases. Right-wing outlets often emphasized stereotypical traits, portraying Ocasio-Cortez as overly emotional or inexperienced, reinforcing traditional gender roles. In contrast, left-leaning outlets framed her actions as calculated and strategic, albeit selectively omitting details that might provoke backlash. These biases, though subtle, significantly shape narratives, impacting public trust and female political representation. As few studies explore how identity aspects intersect to drive media bias toward female politicians, this study calls attention to the compounding effect on bias created by the connection between various identity aspects such as gender, age, socioeconomic class, and political ideology. The research highlights the pervasive nature of identity-based discrimination in political journalism by dissecting linguistic markers and framing tactics. The study also underscores the necessity for balanced reporting practices to reduce biased portrayals and calls for more critical media consumption to avoid echo chambers that perpetuate stereotypes. The findings contribute to the broader understanding of how intersectionality influences media narratives, offering global insights into fostering equitable journalism. This analysis further sheds light on the intersection of identity and power in media discourses, particularly during electoral periods when public perceptions are most malleable.